Fuzzy-set social science - Ragin, Charles C. (University of Chicago, 2000)
In this innovative approach to the practice of social science, Charles Ragin explores the use of fuzzy sets to bridge the divide between quantitative and qualitative methods. Paradoxically, the fuzzy set is a powerful tool because it replaces an unwieldy, "fuzzy" instrumentÑthe variable, which establishes only the positions of cases relative to each other, with a precise oneÑdegree of membership in a well-defined set.